Dissociation of heart rate variability and heart rate recovery in well-trained athletes - Lee, C. M.; Mendoza, A. (European Journal of Applied Physiology, 2012)
The purpose of this investigation was to examine the relationships between aerobic fitness, volume of physical activity (PA), heart rate variability (HRV), and heart rate recovery (HRR) in a group of well-trained endurance athletes. Nineteen endurance athletes participated in this study and had aerobic capacities that placed them above the 99th percentile based on normative values (VO2max: 67.1 ± 2 ml/kg min-1). HRV was obtained via an EKG collected during supine rest and reported as high-frequency (HF), low-frequency (LF), and total power (TP). Natural log (ln) transformation was applied when variables violated assumptions of normality. HRR recovery was reported as the reduction in heart rate from peak exercise to the heart rate 1 min after cessation of exercise and PA was estimated from a questionnaire. HRR was significantly correlated with PA and VO2max (r = 0.67, P = 0.003 and 0.51, P = 0.039, respectively), but not with any index of HRV. Age was significantly correlated with lnHF (r = -0.49, P = 0.033), lnLF/lnHF (r = 0.48, P = 0.037), and normalized units (NU) of LF (r = 0.47, P = 0.042) and HF (r = -0.47, P = 0.042). Stepwise regression revealed that the strongest predictor of HRR was PA (R 2 = 0.45) and that VO2max did not add significant predictive value to the model. The relationship between HRV and age is evident in well-trained endurance athletes, whereas the relationship between HRV and PA/aerobic fitness is not. The maintained relationship between HRR and PA/aerobic fitness suggests that HRR may be a better marker of fitness-related differences in autonomic control in this population.